Markets and Mindwork - Derek C. Bok (Washington University Journal of Law & Policy, 2002)
Competition is pervasive in America. It is almost blasphemous to question its efficacy in ordering human affairs. Despite this wave of popularity, I question how beneficial competition is for institutions that traffic in the work of the mind. Cervantes asks, “Can we ever have too much of a good thing?” I would suggest that there can be too much competition in intellectual pursuits. At least, in these fields of endeavor—including law and education—there is no invisible hand that automatically guides human activity to optimum results. On the contrary, intellectual services share certain characteristics that make competition highly problematic unless great care is applied. In fact, competition is already doing some damage to America’s three most prominent intellectual institutions: public schools, universities, and law firms.
Keywords: Practice of law; Antitrust law; Law schools; United States; Capitalism